2020
DOI: 10.1101/2020.03.27.20044941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating insulin-like growth factor-I, total and free testosterone concentrations and prostate cancer risk in 200,000 men in UK Biobank

Abstract: Background: Insulin-like growth factor-I (IGF-I) and testosterone have been implicated in prostate cancer aetiology. Using newly available data from a large prospective full-cohort with standardised assays and repeat blood measurements, and genetic data from an international consortium, we aimed to investigate the associations of circulating concentrations of IGF-I, sex hormone-binding globulin (SHBG), total and calculated free testosterone with prostate cancer risk. Patients and methods: For prospective analy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Associations with breast, colorectal and prostate cancer have been reported previously in UK Biobank and in separate large nested case-control studies pooling data from several cohort studies (2-4,7-9). Mendelian randomization studies further support that these associations are unlikely to be the result of reverse causality (7)(8)(9). The association between IGF-I concentration and thyroid cancer concurs with previous findings of a positive association reported in the European Prospective Investigation into Cancer and Nutrition (EPIC) (24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Associations with breast, colorectal and prostate cancer have been reported previously in UK Biobank and in separate large nested case-control studies pooling data from several cohort studies (2-4,7-9). Mendelian randomization studies further support that these associations are unlikely to be the result of reverse causality (7)(8)(9). The association between IGF-I concentration and thyroid cancer concurs with previous findings of a positive association reported in the European Prospective Investigation into Cancer and Nutrition (EPIC) (24).…”
Section: Discussionsupporting
confidence: 89%
“…Insulin-like growth factor-I (IGF-I) might be associated with cancer risk due to its role in cell proliferation, differentiation, metabolism and apoptosis, and in angiogenesis (1). In large pooled nested case-control studies and meta-analyses, pre-diagnostic circulating IGF-I concentrations have been shown to be positively associated with colorectal cancer (2), breast cancer (3) and prostate cancer (4) and not associated with lung cancer risk (5,6), and there is recent evidence from Mendelian randomization analyses suggesting that the positive associations may be causal (7)(8)(9). However, evidence for a role of IGF-I in the development of less common cancers is relatively limited, with some data for cancers of the esophagus (10), stomach (11), liver (12)(13)(14), biliary tract (15), pancreas (16), malignant melanoma (17), endometrium (18,19), kidney (20), bladder (21), brain (22,23), thyroid (24), and lymphoma (25).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed associations between free testosterone and prostate cancer risk and an inverse association with SHBG in UK Biobank, and in an international consortium of 20 cohorts (6,933 cases and 12,088 controls)(7,8). These associations are consistent with evidence from two large randomised controlled trials (which aimed to reduce intra-prostatic androgen signalling)(40,41) and a Mendelian randomization study(9).…”
Section: Discussionmentioning
confidence: 95%
“…However, aside from prostate (7)(8)(9), breast (9)(10)(11), and endometrial (9,12,13) cancers, previous population-based observational with hormone measurements have had limited power to assess associations with other cancer sites (4,5,14). Current evidence of associations with other cancers is largely based on animal models and tumor cell lines (15)(16)(17), or investigated indirectly via associations with self-reported menstrual and reproductive factors in women (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that higher serum IGF-I levels is associated with a higher risk of benign prostatic hypertrophy (BPH) [21] and prostate cancer [22,23]. Paradoxically, as men age, serum IGF-I levels decline [24] whereas the incidence of prostate diseases increases [25,26].…”
Section: Introductionmentioning
confidence: 99%